High temperature in-situ synchrotron X-ray diffraction technique of thermal barrier coatings under thermal gradient and mechanical loads - Ruhao Zhou; Bo Sun; Huangyue Cai; Chun Li; Yanling Pei; Xingyu Gao; Ke Yang; Yong Shang; Xiaofeng Zhao; Shusuo Li; Renzhong Tai; Shengkai Gong; et al. (Journal of Materials Research and Technology)
Thermal barrier coatings (TBCs) are commonly used for thermal protection in aero-engine and gas turbine. TBCs are in service under severe environments where high temperatures and high loads, as well as large thermal gradients. Reproducing this service environment of TBCs by in-situ laboratorial setup is essential to the investigation of TBCs failure mechanism. Here we report a thermal gradient mechanical device for the in-situ high-energy synchrotron X-ray diffraction strain measurement. I-shaped samples, with plasma spray physical vapor deposited coatings, were tested with backside cooling and frontside heating under various controlled circumstances. The in-situ strains show that there is a strain gradient within the coating, and the strain change is most pronounced at the topcoat/bond coat interface. Results of this study demonstrate that variations in these conditions create corresponding trends in depth-resolved strains with the largest effects displayed at or near the interface with the bond coat. Temporal- and space-resolved strain distributions of TBCs in near-service environments based on previous studies that have not been publicly reported were obtained, which are essential for the application of validated models of material behavior in extreme environments and for the inverse correction of the preparation process parameters.